Analisis Kinerja Keuangan Pada Unit Usaha Simpan Pinjam BUM Desa Arta Dharma Duta Menanga Periode 2019-2021 - Vidyaningsih, Pande Nyoman Trisna; Adiputra, I Made Pradana (Universitas Pendidikan Ganesha, 2022)
This study aimed to find out how the mechanism for evaluating the financial performance of BUM Desa and how the financial performance of savings and loan business units during the 2019-2021 period. The research method used was a qualitative research method using primary and secondary data. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. To obtain accurate and reliable data, a data validity test would be conducted. The results of this study indicated that the financial performance assessment of BUM Desa had been generally carried out for all business units by supervisors by analyzing consolidated reports to be reported at the Village Deliberation. This study also showed that the results of the assessment of the financial performance of the savings and loan business unit in terms of liquidity (LDR), capital (CAR), operating efficiency (BOPO), and profitability (ROA) were in the healthy category because the results of the calculation of financial ratios obtained a good presentation according to the established measurement standards